Brooding fathers actively consume viable embryos to take up nutrients in a monogamous syngnathid fish - Lin, Tingting; Liu, Xin; Li, Siping; Zhang, Dong; Shen, Fengyuan (Frontiers in Marine Science, 2024)
Syngnathid fishes often experience a reduction in brood size and an increase in immunity during pregnancy. Researchers have studied the polygamous broad-nosed pipefish (Syngnathus typhle) and revealed that some eggs from low-quality females in the male’s brood pouch serve as nurse eggs that are absorbed by the father. It is unclear whether nurse eggs also exist in other syngnathid fishes, especially in monogamous syngnathid fishes. In monogamous syngnathid fishes, the male pouch only carries eggs from a single female. Thus, the question remains: do some eggs of monogamous syngnathid fishes also serve as nurse eggs? And if so, are these nurse eggs impaired eggs, or are they viable eggs that are consumed by the brooding father? In the present study, we used the monogamous lined seahorse (Hippocampus erectus) and asked whether nurse eggs exist in this species. We also explored whether nurse eggs potentially originate from viable versus inviable eggs. Using isotope labeling, we found that nutrients from embryos could be transferred to brooding fathers. Furthermore, we also found that brooding fathers with limited food had a higher isotope content and a smaller brood size compared to individuals with sufficient food. These results have demonstrated that nurse eggs exist in the lined seahorse, and also suggested that the brooding fathers actively consume viable embryos to absorb nutrients in response to low food availability. These findings help us better understand parent–embryo conflict, filial cannibalism, and male-only care in teleost fishes.